TOURISM: ON THE EXAMPLE OF THE SHRINES OF THE FERGHANA - Turaboyeva Yara Rustamdjonovna (Web of Journals Publishing, 2024)
The article attempts to show the significance and role of shrines, as well as shrines that further enrich the unique tourist attraction of the Ferghana Valley. Ferghana shrines are also important for their antiquity, value for the local population and special value for domestic tourism.
Keywords: Pilgrimage tour, Sayru Suluk, Sultan Uwais Karaniy Shrine, qalandarkhan, eyvokhbuva Shrine, Grandfather Carrizi Shrine in Ferghana region, Khoja Algar Shrine, Khojanazar Huwaido shrine.